The Tahlil Quran as a Medium for Spiritual Strengthening and a Symbol of Unity in Banduarjo Hamlet, Sumberpetung Village, Kalipare District: A Living Quran Study: Tahlil Quran Sebagai Media Penguat Kerohanian dan Simbol Persatuan: Kajian Living Quran - Rizqi Mawani, Juhiran; Ayu Lestari, Putri; Fatih Rabbani, ⁠Muhammad; Jibril, Hosianda; Salsabilla, Rahma; wasimatul hurriyah, Atika (Lembaga Pendidikan Ma'arif Nahdlatul Ulama, Kabupaten Malang, Indonesia, 2025)
The External Quality Assurance System (SPME) is a mechanism designed to ensure that educational institutions comply with the National Education Standards (SNP) through assessments conducted by external bodies such as BAN-PT for universities and BAN-S/M for schools/madrasas. SPME aims to provide quality assurance to the public by evaluating key aspects such as governance, curriculum quality, educator competence, infrastructure, and user satisfaction. This study uses literature review techniques to analyze various secondary sources such as journals, articles, and official documents related to the implementation of SPME in educational institutions. Data were analyzed using a content analysis approach to identify the implementation of SPME. The research findings revealed that SPME not only functions as a performance evaluation tool for educational institutions but also as a strategic guideline in building a sustainable quality culture. SPME enables educational institutions to address weaknesses, improve the quality of their services, and strengthen their competitiveness at the national and international levels. However, the success of this system highly depends on the support of qualified human resources, management commitment, and the provision of appropriate equipment and budget.